12-HHT is associated with epithelial barrier enhancement and reduced inflammatory responses in colon organoids of normoganglionosis in Hirschsprung’s disease - Kazuto Suda; Kumpei Abe; Yurina Nishimura; Masafumi Tanaka; Yuki Nagasako; Xuxuan Rao; Jianqin Zhang; Siyi Zeng; Kentaro Fujiwara; Shunsuke Yamada; Junya Ishii; Shiho Yoshida; et al. (PLoS ONE, 2026)
Purpose Hirschsprung-associated enterocolitis remains a major postoperative complication of Hirschsprung’s disease (HD), and impaired epithelial barrier integrity has been proposed as a contributing factor. In this study, we investigated whether 12-hydroxyheptadecatrienoic acid (12-HHT), an endogenous leukotriene B4 receptor 2 (BLT2) agonist, is associated with epithelial barrier enhancement and reduced inflammatory responses in patient-derived colonic organoids. Methods Normoganglionic specimens from rectal/rectosigmoid HD at pull-through (HD-N; n = 8) and transverse colon specimens from anorectal malformation (ARM) at colostomy closure (n = 10) were used to generate colonic organoids. Epithelia were isolated using ethylenediaminetetraacetic acid and subsequently embedded in Matrigel. Baseline expression of TJP1 , TJP2 , F11R (encoding junctional adhesion molecule-A), JAM2 , CLDN1 , CLDN3 , CLDN4 ) and LTB4R2 (encoding BLT2) was assessed by qPCR and immunoblotting. Organoids were then treated with 12-HHT (0.4, 2, or 10 μM) for 7 days, followed by qPCR. Additional experiments assessed cytokine expression ( IL1B , IL6 ) and TJPs after 24 h with tumor necrosis factor-α (TNF-α, 100 ng/mL) plus phosphate buffered saline or 12-HHT. Barrier function was evaluated using FITC–dextran influx assays. Results HD-N and ARM organoids exhibited similar growth efficiencies. Baseline expression for F11R , JAM2 , CLDN1 , CLDN3 , CLDN4 , and LTB4R2 was significantly lower in HD-N than in ARM. TJPs were upregulated by 12-HHT at 2 and 10 μM in both groups, with stronger effects in ARM. In HD-N organoids, 10 μM 12-HHT suppressed TNF-α-induced IL1B and IL6 elevation mitigated tight junction proteins (TJPs) downregulation more effectively than 2 μM. 12-HHT attenuated TNF-α–induced FITC–dextran influx in HD-N organoids. Conclusion 12-HHT is associated with epithelial barrier enhancement and reduced inflammatory responses in HD-N organoids.